Pengaruh Employee Engagement terhadap Kepuasan Kerja dengan Work Life Balance sebagai Variabel Intervening - Noufal Ahmadi Atthohiri; Dewie Tri Wijayati (Jurnal Ilmu Manajemen, 2021)
Land public transportation modes are experiencing a significant increase after constructing the Trans Java toll road. Many bus companies maximize the use of the Trans Java toll road to serve the community, one of these companies is PT. Haryanto Motor Indonesia. This company is engaged in Autobus Transportation. This study aims to determine the effect of employee engagement on job satisfaction with work-life balance as an intervening variable. This type of research is quantitative with 66 employees using purposive sampling technique with criteria is all of the respondents have worked in east java. The statistical analysis technique used is Partial Least Square with the help of SmartPLS 3 software. The results obtained from the study explain that employee engagement has a positive but not significant effect on job satisfaction, employee engagement has a positive and significant effect on work-life balance, work-life balance has a significant positive effect. On job satisfaction and work-life balance can mediate with full mediation category. The implication of this research is in terms of job satisfaction; the company may be able to add labour guarantees to its employees to increase the sense of security and satisfaction of the employees.